Counseling on The Use of Nesting For Low Birth Weight (LBW) Babies in The Perinatology Room of Banten Province Hospital - Annisa Rahmawati; Herti Eka Herawati; Ms. Zahrah Maulidia Septimar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Introduction Birth weight is the weight of a baby one hour after birth. Normal birth weight is between 2500-4000 grams , while babies with birth weight <2500 are said to be low birth weight (LBW). Babies born with low birth weight are generally less able to absorb new environmental pressures, which can result in stunted growth and development, and can interfere with their survival. Treatment that can be given to low birth weight (LBW) babies is with non-pharmacological therapy, which consists of baby massage, music therapy, kangaroo method care, and nesting. Nesting is a tool that has a shape similar to the mother's womb, which is used as a treatment to reduce LBW. According to the World Health Organization (WHO), 5-10% of babies in Indonesia experience LBW, in addition, according to the Indonesian Ministry of Health, LBW is one of the causes of increasing infant mortality rates, namely 35.5% of neonatal deaths in Indonesia. In 2023, there were 14.95% of babies in Banten Province who had low birth weight (LBW) babies. The purpose of this activity is to provide knowledge to parents of babies regarding the benefits of using nesting for low birth weight (LBW) babies . The activity was carried out at the Banten Regional General Hospital in the Perinatology room, which was attended by mothers as parents of LBW baby patients. The method of the activity carried out was by providing questions about the benefits of nesting at the beginning and end of the activity, providing counseling materials related to the benefits of nesting for LBW, and also demonstrating activities on how to make nesting in a simple way that can be done at home. The activity took place for one day in June 2024. The results of this activity were that the families of LBW patients understood that LBW can be controlled through the nesting method , families can demonstrate nesting independently, and also increase family knowledge regarding the benefits of nesting. So it can be concluded from this counseling activity, namely the nesting method can provide good sleep quality for LBW.